The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10633-010-9230-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials to pattern, motion and cognitive stimuli in Alzheimer’s disease

Abstract: The aim of our study was to verify reported visual dysfunctions of patients with Alzheimer disease with the use of several variants of VEPs and visual ERPs and to learn whether these methods can be useful in diagnostics of AD. We tested 15 patients (6 women and 9 men, aged from 58 to 87) with mild to moderate Alzheimer disease (12-23 points of Mini Mental State Examination) and 15 age, gender and education level matched controls. The examination consisted of VEPs to pattern-reversal and motion-onset stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…Thus, motion processing deficits in AD do not reflect broad declines across global visual processing mechanisms. This reinforces previous reports suggesting more disruption to classic dorsal stream functioning than ventral stream in AD (Nguyen et al, 2003;Sartucci et al, 2010;Kubová et al, 2010), and explains why many more studies claim complex motion-related deficits than form-related deficits in these patients. The patterns reported here for AD are similar to those found in developmental disorders in childhood using the same methodology (Spencer et al, 2000;Atkinson et al, 2006), and they allow us to extend the concept of "dorsal stream vulnerability" (Braddick et al, 2003) into disorders of old age.…”
Section: Motion Vs Form Comparedsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, motion processing deficits in AD do not reflect broad declines across global visual processing mechanisms. This reinforces previous reports suggesting more disruption to classic dorsal stream functioning than ventral stream in AD (Nguyen et al, 2003;Sartucci et al, 2010;Kubová et al, 2010), and explains why many more studies claim complex motion-related deficits than form-related deficits in these patients. The patterns reported here for AD are similar to those found in developmental disorders in childhood using the same methodology (Spencer et al, 2000;Atkinson et al, 2006), and they allow us to extend the concept of "dorsal stream vulnerability" (Braddick et al, 2003) into disorders of old age.…”
Section: Motion Vs Form Comparedsupporting
confidence: 91%
“…Bokde et al (2010) used fMRI to show that, compared with controls, AD patients recruit additional brain areas when performing location-matching but not face-matching tasks. Similarly, Kubová et al (2010) and Sartucci et al (2010) report a reduced amplitude of EEG response in AD patients versus controls to radial optic flow, and high contrast luminance gratings reversed at high temporal frequency ("dorsal stream"), but not stimuli thought to represent ventral stream processing. Overall, while form-based impairments may occur in AD, the evidence is of lesser magnitude and consistency than the evidence for decline in motion systems.…”
Section: Motion and Form In Alzheimer's Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…Thus, our findings link age-related delays in a behavioral tasks [42] to prolonged ERP latencies [43], and AD related perceptual impairments [44] to reductions in ERP amplitudes [45]. As a result, we must conclude that aging and AD are distinguishable processes.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, the AD patients showed greater activation in the inferior parietal lobule and recruitment of additional regions. Moreover, recent EEG studies have used visual [86] and auditory [87•] oddball tests to elicit event-related potentials (ERPs) with AD and MCI patients. Both of these studies revealed that the latencies of ERPs in AD and MCI patients were significantly more prolonged than that of normal individuals.…”
Section: Deficits In Non-memory-based Cognitive Domainsmentioning
confidence: 99%